You need to evaluate the product of the vectors `u = u_x*i + u_y*j, v = v_x*i + v_y*j` , such that:

`u*v = u_x*v_x + u_y*v_y`

`u*v = (3)*(-2) + 2*(-3)`

`u*v = -6 - 6`

`u*v = -12`

** Hence, evaluating the product of the vectors `u = u_x*i...**

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to evaluate the product of the vectors `u = u_x*i + u_y*j, v = v_x*i + v_y*j` , such that:

`u*v = u_x*v_x + u_y*v_y`

`u*v = (3)*(-2) + 2*(-3)`

`u*v = -6 - 6`

`u*v = -12`

**Hence, evaluating the product of the vectors `u = u_x*i + u_y*j, v = v_x*i + v_y*j,u = <3,2>, v = <-2,-3>,` yields `u*v = -12.` **